Affordances and agricultural technology. (August 2022) - Glover, Dominic
Abstract: This paper discusses how the theory of affordances can be used to investigate how a spectrum of opportunities, benefits, costs and risks is generated and unevenly distributed by different kinds of technology (where 'technology' is understood as techniques, processes and practices of doing and making, rather than technical artefacts and systems). Affordances are possibilities for action, which arise from relations between humans and entities that surround them. This paper discusses three kinds of affordances: material, cultural and socio-economic. The theory of affordances offers a coherent way to explain why different technologies have different implications, and why those implications vary for different stakeholders. Applied to the domain of development-oriented agricultural research and innovation, the theory of affordances could be used by researchers and practitioners to examine the differentiated implications of different kinds of farming technology and alternative programmes of technological change in agriculture, both ex ante (e.g. in their design, development and implementation) and ex post (e.g. in their evaluation). To illustrate the argument, the paper uses the example of weeding in the System of Rice Intensification. Since affordances in theory are generated relationally and situationally for each person, the full array of implications arising from the introduction of new technology could be wide and diverse. A practical challenge, therefore, is whether and how the theory of affordances can be used practically and operationally to design, implement and evaluate the appropriateness, accessibility, utility and value of agricultural technology and technological change for specific people and groups of interest. Highlights: The theory of affordances is applied to agricultural technology and innovation. Affordances are perceived action possibilities, which arise relationally. Affordances can be studied through material, cultural and socio-economic lenses. The theory of affordances could be applied to development interventions ex ante and ex post. Weeding in the System of Rice Intensification is used to illustrate the argument.